A model of university social responsibility: a proposal for the Colombian institutions - Forero-Jiménez, Martha Yaneth (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This article is the result of an investigation whose objective was to propose a model to implement the RSU (University Social Responsibility) from a brief analysis of its situation in Colombia. Qualitative research was applied, specifically descriptive-explanatory, using the Shewhart cycle, resulting in the proposed model composed by the four pillars of higher education: teaching, social projection, research and management, plus environment and post-conflict. Environment, despite being part of the social responsibility scheme, is hardly being treated with any rigor in literature and post-conflict is of great relevance given the current reality of Colombia. In parallel, the table of indicators was designed, which became a key tool to know the status of each university with respect to its social commitment and consequently take measures to improve it. Finally, it is concluded that one of the causes of the lack of implementation is due to the lack of a methodology or a model of how to do it, as well as the lack of interest, because we have not become aware of its importance and how favorable it is to contribute to the reconstruction of the fabric of society.